Analisis Pengaruh Semangat Kerja, Promosi Jabatan dan Kompetensi Terhadap Kinerja ASN di Sekretariat Daerah Kabupaten Simeulue - Muhammad Yayan (P4M STIE Putra Bangsa, 2021)
Abstract The problem in this study is that the performance of the Regional Secretariat of Simeulue Regency is still not optimal, this is motivated by the not yet maximal application of the Job Promotion variable while the Work Spirit and Competence variables are considered to have been running well as a State Civil Apparatus. The purpose of this study was to analyze the influence of work morale, position promotion and competence on the performance of ASN at the Regional Secretariat of Simeulue Regency either simultaneously or partially. The research method used is a quantitative survey research method with a population of 87 people, namely all employees both in positions and at the staff level. The type of data or information used is primary data with data collection techniques through questionnaires and literature studies. The data analysis technique was carried out using a data analysis approach of validity, reliability and classical assumption test, then multiple linear regression analysis, determination test, simultaneous test and partial test were carried out. The findings from the results of this study simultaneously the variables of Work Morale, Position Promotion and Competence have a positive effect on improving performance. while partially, only two independent variables have a positive effect, namely the work spirit variable and the competence variable, while the job promotion variable has no positive effect on performance, this is influenced by other indicators outside the analysis of this study.